2016
DOI: 10.1117/1.jbo.21.7.071113
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivoMueller polarimetric imaging of the uterine cervix: a first statistical evaluation

Abstract: Early detection through screening plays a major role in reducing the impact of cervical cancer on patients. When detected before the invasive stage, precancerous lesions can be eliminated with very limited surgery. Polarimetric imaging is a potential alternative to the standard screening methods currently used. In a previous proof-of-concept study, significant contrasts have been found in polarimetric images acquired for healthy and precancerous regions of excised cervical tissue. To quantify the ability of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 26 publications
0
62
0
Order By: Relevance
“…Previous studies showed that the relevant polarimetric parameters for analyzing the uterine cervix microstructure were the Depolarization (Δ) and Retardance (R) 12, 14 . Depolarization enables one to evaluate the scattering properties of tissue while Retardance to quantify its anisotropy, generally due to the presence of collagen fibers, which are known to be strongly birefringent.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that the relevant polarimetric parameters for analyzing the uterine cervix microstructure were the Depolarization (Δ) and Retardance (R) 12, 14 . Depolarization enables one to evaluate the scattering properties of tissue while Retardance to quantify its anisotropy, generally due to the presence of collagen fibers, which are known to be strongly birefringent.…”
Section: Resultsmentioning
confidence: 99%
“…13,14 It may be pertinent to note, in this regard, that recent studies have also demonstrated that changes in tissue birefringence property (quantified from MM) are related to morphological changes in cervical precancers. 15,16 In our approach, we have therefore employed Born approximation-based Fourier domain preprocessing 4 on wavelength variation of the selected MM elements (those encode the linear birefringence information). Such preprocessing captures information on the statistically equivalent spatial RI fluctuations of the anisotropic layer.…”
Section: Introductionmentioning
confidence: 99%
“…MM encodes two basic anisotropy properties, namely, the retardance (birefringence) and the diattenuation (dichroism). 15,16 The former represents phase anisotropy (differential phase between orthogonal polarization), anisotropy in real part of the RI, and the latter represent amplitude anisotropy (differential attenuation via scattering and/or absorption between orthogonal polarization). 13,14 In this study, backscattering spectral Mueller matrices were recorded and subsequently decomposed to extract the linear retardance parameter.…”
Section: Introductionmentioning
confidence: 99%
“…In prior work a proof-of-concept study demonstrated significant contrast in Mueller polarimetric images acquired for healthy and pre-cancerous regions of excised cervical tissue [1]. To quantify the ability of this modality to differentiate between healthy and pre-cancerous tissue, polarimetric Mueller images of seventeen cervical specimens were compared to results from histopathology; excised tissue shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In this prior work an optimized value of 83% was achieved for both sensitivity and specificity for images acquired at 450nm and for a threshold scalar retardance value of 10.6. 1 In this work we aim to improve this detection performance by using a novel classification algorithms designed to compute quadratic classifiers from high-dimensional image data. This J-optimal channelized quadratic observer (J-CQO) is an algorithm that can incorporate all polarimetric, spectral, and local spatial measurements into the classifier.…”
Section: Introductionmentioning
confidence: 99%